Attachment and Tendency of Schizophrenia Sufferers to Crime in the Study of Criminology and Islamic Law - Fachrul Maula; Soraya Devy; Azmil Umur (LifeSciFi, 2026)
This research is motivated by increasing public concern regarding the relationship between schizophrenia and crime, which is often oversimplified and burdened with social stigma. The study aims to analyze the linkage and tendencies of individuals with schizophrenia toward criminal behavior through a comprehensive perspective of criminology and Islamic law. This research employs a qualitative field study approach, supported by in-depth interviews, observations, and analysis of criminology, psychiatry, and Islamic law literature. The findings indicate that the tendency to commit crime among individuals with schizophrenia is not deterministic, but rather influenced by the interaction between internal factors, such as neurobiological and psychological disorders, including persecutory delusions and auditory hallucinations, and external factors, including stigma, discrimination, and weak social support. Criminal behavior tends to be reactive and situational rather than a manifestation of conscious criminal intent. From an Islamic legal perspective, individuals with schizophrenia cannot be fully held criminally responsible based on the principles of ahliyah and maqāṣid sharia. The implications highlight the need for a shift toward preventive, rehabilitative, and humanistic approaches. In conclusion, a comprehensive understanding is essential to reduce stigma and ensure sustainable social security and welfare.